1996
DOI: 10.1029/95jc02829
|View full text |Cite
|
Sign up to set email alerts
|

The stable isotope composition of waters of the eastern Mediterranean Sea

Abstract: Waters of the eastern Mediterranean portray an unusual pattern of stable isotope composition compared with other evaporitic systems: an increase in 18O concentration up to value of δ18O = +2.2‰ is not matched by a commensurate increase of deuterium. It is shown that this unusual pattern is an expression of the “medi‐terranean” location of the sea, where the air‐sea interaction with relatively dry and isotopically depleted continental air masses dominates the evaporation process in winter and where the diluting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
5
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 16 publications
7
117
5
4
Order By: Relevance
“…Water circulation over the EM shelf is northward throughout the year with strong seasonal variability. The shelf and slope current system are part of the Levantine basin's general circulation, which is composed of the Atlantic Ionian stream, the Mid-Mediterranean Jet, and the cyclonic basin-wide current that follows the coast [Gat et al, 1996;Hecht et al, 1988]. In summer, the strong currents are confined to the upper layer with seaward intensification.…”
Section: General Site Descriptionmentioning
confidence: 99%
“…Water circulation over the EM shelf is northward throughout the year with strong seasonal variability. The shelf and slope current system are part of the Levantine basin's general circulation, which is composed of the Atlantic Ionian stream, the Mid-Mediterranean Jet, and the cyclonic basin-wide current that follows the coast [Gat et al, 1996;Hecht et al, 1988]. In summer, the strong currents are confined to the upper layer with seaward intensification.…”
Section: General Site Descriptionmentioning
confidence: 99%
“…The calculated isotopic ratios of fluids in equilibrium with illite-water fractionation factors (Savin and Lee, 1988 Gat et al, 1996) (Fig. 12).…”
Section: Stable Isotopesmentioning
confidence: 99%
“…Some studies have shown that slopes smaller than 8, which characterize the GMWL and EMMWL lines, are typical for mixing and evaporating systems (e.g., [29,[36][37][38]). In a specific study, a slope of 4.3 was measured for water systems under controlled evaporating conditions [36].…”
Section: Isotopic Composition Of the Main Water Sources And Of The Namentioning
confidence: 99%
“…Water molecule isotopic compositions: (a) the Shafdan system, including the recharged effluents (PS-6 or at the ponds) and the recovery wells (RW); and (b) the freshwater sources, in the National Water Carrier (NWC) and in the Shafdan system. Isotope data for the Coastal Aquifer, Mountain Aquifer, Mediterranean Sea, desalinated water (DSP), and for the Sea of Galilee (SOG) were taken from previous works [3,5,8,[29][30][31][32][33][34][35]. The secondary effluents compose the heavier end-member, with δ 18 O of −1.5 ± 0.1 and δ 2 H of −4.9 ± 0.9 for 2010-2011 campaign, and δ 18 O of −1.4 ± 0.2 and δ 2 H of −1.2 ± 1.3 for 2014 campaign (Table 3).…”
Section: Isotopic Composition Of the Shafdan Systemmentioning
confidence: 99%
See 1 more Smart Citation